2013
DOI: 10.1037/a0030244
|View full text |Cite
|
Sign up to set email alerts
|

Family income and early achievement across the urban–rural continuum.

Abstract: Rural and suburban children account for the majority of poor children in the United States. Yet, most research examining poverty's associations with child development is focused on urban samples. Using nationally representative data from the Early Childhood Longitudinal Study, Birth Cohort (N ≈ 6,600), this study examines whether the form and magnitude of income's relationship with early achievement differ across the urban-rural continuum. Results suggest that there are urbanicity-related differences in the fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 37 publications
(70 reference statements)
3
40
0
Order By: Relevance
“…In China, urban-rural differences have been found in the growth of breastfed babies, with those living in cities showing significantly greater weight, length and head circumference than those in rural areas [31]; urban and urbanized children have also been found to be more socially adjusted in school [32]. In the United States, increases in income were associated with great improvements in early academic skills in urban areas, but only slight improvements in rural areas [33]. As in previous studies, socioeconomic condition has been found to be an important confounding factor in child development: the level of education of the parents has been associated with the developmental condition of the children [34,35].…”
Section: Resultsmentioning
confidence: 99%
“…In China, urban-rural differences have been found in the growth of breastfed babies, with those living in cities showing significantly greater weight, length and head circumference than those in rural areas [31]; urban and urbanized children have also been found to be more socially adjusted in school [32]. In the United States, increases in income were associated with great improvements in early academic skills in urban areas, but only slight improvements in rural areas [33]. As in previous studies, socioeconomic condition has been found to be an important confounding factor in child development: the level of education of the parents has been associated with the developmental condition of the children [34,35].…”
Section: Resultsmentioning
confidence: 99%
“…Recent conceptualizations of poverty suggest that the precise types of community-level, environmental stressors for those living in poverty vary by level of urbanicity, with most research in this area conducted on children from large urban communities (Miller, Votruba-Drzal, & Setodji, 2013; Shaw, 2013). Urban, suburban, and rural areas differ in terms of their population density, resources, availability of transportation, and social and community capital.…”
Section: Discussionmentioning
confidence: 99%
“…Relatedly, the precise types of community-level, environmental stressors for those living in poverty vary by level of urbanicity, with most research in this area conducted on children from large urban communities (Miller, Votruba-Drzal, & Setodji, in press). Urban, suburban, and rural areas differ in terms of their population density, resources, availability of transportation, and social and community capital.…”
Section: Future Directions For Research On the Development Of Early Cmentioning
confidence: 99%
“…Urban, suburban, and rural areas differ in terms of their population density, resources, availability of transportation, and social and community capital. Rural communities are often characterized by lack of access to public transportation, health care, libraries, child care, and other social services (Vernon-Feagans, Gallagher, & Kainz, 2008), inner-city neighborhoods often include little green spaces, high rates of crime and poverty concentration, overcrowding, and noise and air pollution (Evans, 2006), while low-income families living in suburban communities report feeling isolated from social service providers and social support (Miller et al, in press). It remains to be seen how these differences in urbanicity relate to the development and persistence of CP.…”
Section: Future Directions For Research On the Development Of Early Cmentioning
confidence: 99%